2011
DOI: 10.1098/rsfs.2010.0029
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular modelling: a quantitative functional assessment tool based on cardiac magnetic resonance imaging

Abstract: We present the development and testing of a semi-automated tool to support the diagnosis of left ventricle (LV) dysfunctions from cardiac magnetic resonance (CMR). CMR short-axis images of the LVs were obtained in 15 patients and processed to detect endocardial and epicardial contours and compute volume, mass and regional wall motion (WM). Results were compared with those obtained from manual tracing by an expert cardiologist. Nearest neighbour tracking and finite-element theory were merged to calculate local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Late gadolinium-enhancement images for scar detection were obtained 10 minutes after intravenous infusion of gadolinium (Gadobutrol, 0.2 mmol/kg body weight) using a T-weighted gradient-echo pulse sequence with a phase-sensitive inversion recovery reconstruction. Semi-automatic segmentation of ventricular epicardium and endocardium was performed as described in a previous study [12]. Atrial cavities, aorta, inferior and superior vena cava, and pulmonary trunk were manually segmented using custom-made software for tracing contours.…”
Section: Model Constructionmentioning
confidence: 99%
“…Late gadolinium-enhancement images for scar detection were obtained 10 minutes after intravenous infusion of gadolinium (Gadobutrol, 0.2 mmol/kg body weight) using a T-weighted gradient-echo pulse sequence with a phase-sensitive inversion recovery reconstruction. Semi-automatic segmentation of ventricular epicardium and endocardium was performed as described in a previous study [12]. Atrial cavities, aorta, inferior and superior vena cava, and pulmonary trunk were manually segmented using custom-made software for tracing contours.…”
Section: Model Constructionmentioning
confidence: 99%
“…The estimated strains from the same animals were highly correlated to the values derived from implanted markers. Conti et al (2011) calculated strains with point tracking from cine CMR with a virtual heart phantom, and compared these data with strains from a finite element model. They found that local strains agreed well with the results from finite element modelling.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of obtaining accurate anatomical and functional information from a single imaging modality, the relatively “clean” appearance of the images (in comparison to echocardiography), and the relatively widespread availability of MRI have led to its use in many cardiac modelling studies, e.g. ( Plank et al., 2009; Vadakkumpadan et al., 2009; Conti et al., 2011; Bishop and Plank, 2012; Krishnamurthy et al., 2013 ), as will be illustrated in more detail in Sections 3 and 4 below.…”
Section: Established Clinical Imaging Technologies: An Overviewmentioning
confidence: 99%